The Intensity of Deterioration among the Scheduled Tribes at the Shadow of Globalisation- A Study of Kerala - Haseena V. A (Journal of Law, Policy and Globalization, 2015)
Globalization has become a new term for signifying dramatic changes in the nature of international relations in the latter part of 20th century and dawning of 21st century. Globalization conveys many meanings and things emphasizing a global rather than a national context. It is something like a process by which it redefines the world affairs especially in relations between states. In other words it is the process of increasing interconnectedness between societies such that events in one part of the world have effects on peoples and societies far away. Globalization denotes expanding scale, growing magnitude, speeding up and deepening impact of transcontinental flows and patterns of social interaction. It refers a shift or transformation in the scale of human organization that keeps links among distant communities and expands the reach of power relations across the world’s regions and continents. But it does not pose as a universal process of global integration, in which there is growing convergence of cultures and civilization. As an economic term, it denotes the acceleration of the international connections in the global economy in the last few decades and the emergence of global corporations and relatively open international financial markets6. The word also invokes themes of cultural union as a result of media and electronic interconnections from satellite broad cast, television, fax machines, cyber space etc.Globalisation is the integration of Economic, political and cultural systems across the globe through interactions between nations, with the economic perspective government policies around the globe that have opened economies domestically and internationally, aided by technological development have spurred increases in cross boarder trade, investment and migration so large that many observers believe the world has enter a qualitatively new phase in its economic development. But there are sharp differences on its impact on society. The Indian state of Kerala have had entirely different experience of development process from anywhere else in the country, the much celebrated Kerala model of development has faced enough criticism for excluding the tribals, Dalits, fisher folks and other weaker sections of the state. The present paper argues that It is been accepted that the celebrated kerala model of development has not made much changes for the socio-economic life of the tribals of kerala, by using different secondary data sets the paper argues that after the sixty years of formation of the state tribals continues as one of the most marginalised community within the state, the post globalised developmental projects and developmental dreams of the state has again made the deprivation of the tribals of kerala and the developmental divide has increased between the tribal and non-tribal in the state.